Ectonocryptoides sandrops – a new scolopendromorph centipede from Belize - Schileyko, Arkady A. (Soil Organisms, 2022)
Anew representative of the rare subfamily Ectonocryptopinae (Scolopocryptopidae) is described from western Belize as Ectonocryptoides sandrops sp. nov. Both previously known representatives of this subfamily (Ectonocryptops kraepelini Crabill, 1977 and Ectonocryptiodes quadrimeropus Shelley & Mercurio, 2005) and the new species have been compared and the taxonomic status of the latter has been analysed.
Keywords: Ectonocryptopinae; new species; Belize